2018
DOI: 10.1063/1.5021147
|View full text |Cite
|
Sign up to set email alerts
|

Particle-in-cell simulations of magnetically driven reconnection using laser-powered capacitor coils

Abstract: In this paper, we propose an experimental scheme to fulfill magnetically driven reconnections. Here, two laser beams are focused on a capacitor-coil target and then strong currents are wired in two parallel circular coils. Magnetic reconnection occurs between the two magnetic bubbles created by the currents in the two parallel circular coils. A two-dimensional particle-in-cell simulation model in the cylindrical coordinate is used to investigate such a process, and the simulations are performed in the ðr; zÞ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…It has been demonstrated that the thickness of the electron diffusion region during fast reconnection is on the electron inertia scale (Huang, Lu, Yang, et al, 2011; Huang, Lu, Gao, et al, 2018; Ji et al, 1998; Olson et al, 2016; Wygant et al, 2005), thus we trace the active region of the x‐line using criterion δ < 2 d e , l , that is triggered when the current sheet half‐thickness is thinner than two local electron inertial length. Figure 1c shows the time stacks of the reconnection electric field E y and the current sheet half‐thickness δ along the x‐line; here we use J y to calculate δ .…”
Section: Overview Of the Internal X‐line Asymmetrymentioning
confidence: 99%
“…It has been demonstrated that the thickness of the electron diffusion region during fast reconnection is on the electron inertia scale (Huang, Lu, Yang, et al, 2011; Huang, Lu, Gao, et al, 2018; Ji et al, 1998; Olson et al, 2016; Wygant et al, 2005), thus we trace the active region of the x‐line using criterion δ < 2 d e , l , that is triggered when the current sheet half‐thickness is thinner than two local electron inertial length. Figure 1c shows the time stacks of the reconnection electric field E y and the current sheet half‐thickness δ along the x‐line; here we use J y to calculate δ .…”
Section: Overview Of the Internal X‐line Asymmetrymentioning
confidence: 99%
“…The reason for the formation of J e y is the rapid movement of the magnetic field lines away from the current sheet, and the electrons in the outflow regions are continuously bounced. [30] Electron outflow has been verified as a criterion for reconnection in both simulations and experiments. [49,50] There is no current density in the P-case where no MR occurs.…”
Section: Simulation Resultsmentioning
confidence: 82%
“…Thanks to this experiment configuration, the direct measurement of the nonthermal electrons from MR becomes feasible, [28] which is limited in the dedicated devices like MRX, because of the larger system size compared to the short mean free path and Debye lengths. Experiments [27,29] and kinetic simulations [30,31] depend on this configuration have revealed MR outflow, quadruple magnetic fields, and nonthermal electron acceleration. Different acceleration mechanisms have been studied theoretically and numerically, including direct acceleration of reconnection electric field where the particles drift along the reconnection electric field following the Speiser orbits, [32][33][34] Fermi mechanism that is the particles are reflected in contract magnetic island [35,36] or by the moving magnetic field lines [37,38] and gain kinetic energy, betatron acceleration that is the magnetized electron is accelerated by the perpendicular inductive electric field generated by the enhancement magnetic field, [39][40][41] and parallel electric field acceleration along the magnetic fields.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For these conditions we found through particle tracking studies that the electrons are energized primarily by direct acceleration at the X points, with plasmoid related acceleration contributing only minor additional energy gain. Numerical studies by other groups have shown similar electron acceleration [31][32][33] . Here we extend our study to larger system sizes in terms of the microscopic ion skin depth d i = c/ω pi , which could be produced at megajoule class laser facilities such as NIF.…”
Section: Introductionmentioning
confidence: 62%